2013
DOI: 10.1128/aem.00561-13
|View full text |Cite
|
Sign up to set email alerts
|

An MSH4 Homolog, stpp1 , from Pleurotus pulmonarius Is a “Silver Bullet” for Resolving Problems Caused by Spores in Cultivated Mushrooms

Abstract: The enormous number of spores produced by fruiting bodies during cultivation of mushrooms can lead to allergic reactions of workers, reduction of commercial value, spread of mushroom disease, pollution of facilities, and depletion of genetic diversity in natural populations. A cultivar harboring a sporulation-deficient (sporeless) mutation would be very useful for preventing these problems, but sporeless commercial cultivars are very limited in usefulness because sporeless traits are often linked with traits t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 45 publications
0
27
1
Order By: Relevance
“…In the current study, transcriptome analyses revealed that a large number of genes related to metabolic, cellular, and other biological processes might be involved in spore development were up-or down-regulated in the test strains. The majority of these genes encoded enzymes involved in DNA repair or homologous recombination were down-regulated in the mutant strains; these finding differ from those of previous reports [25]. Additional studies identified the gene fragments CL11 and 11355 as homologs of the DNA repair gene rad 8 in C. cinerea, and these fragments were not expressed in the mycelia or fruiting bodies of the three mutant strains.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…In the current study, transcriptome analyses revealed that a large number of genes related to metabolic, cellular, and other biological processes might be involved in spore development were up-or down-regulated in the test strains. The majority of these genes encoded enzymes involved in DNA repair or homologous recombination were down-regulated in the mutant strains; these finding differ from those of previous reports [25]. Additional studies identified the gene fragments CL11 and 11355 as homologs of the DNA repair gene rad 8 in C. cinerea, and these fragments were not expressed in the mycelia or fruiting bodies of the three mutant strains.…”
Section: Discussioncontrasting
confidence: 81%
“…Although some genetic sites were identified as potentially related to the regulation of spore development, few genes were discovered in these sequences [15,16,25], and only the single gene stpp1, which is an MSH4 homolog in P. pulmonarius, had a verified function after genetic transformation [25]. Therefore, the identification of additional genes that are related to spore generation will provide important evidence for studying the sexual development and breeding of edible fungi.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Omissions of one or the other subroutine or chances within a subroutine will not inevitably fully break down the whole process of fruiting whose ultimate biological target is genetic recombination and the production of meiotic basidiospores. Noteworthy for commercial mushroom cultivation, a block in basidiospore production for example can still give perfectly shaped mushrooms and these can overcome the problems of spore-induced allergies for mushroom growers and consumers (Hasebe et al, 1991;K€ ues et al, 2007;Okuda et al, 2013).…”
Section: Subroutines In Mushroom Formationmentioning
confidence: 98%